Penguatan Kapasitas Sumber Daya Manusia dalam Pengelolaan Atraksi Wisata Air di Danau Maninjau - Sulis Purwanto; Sukma Yudistira; Lise Asnur (BALE LITERASI, 2026)
Tourism is one of the service industries that plays a significant role in improving the economy for local governments, the private sector, and local communities. Economic growth occurs through various activities carried out by stakeholders in delivering services to tourists. However, the development of tourist attractions in Lake Maninjau still faces several challenges, including low community awareness of tourism development, limited utilization of water-based attractions, and inadequate competencies in guiding and safety management for water tourism. These conditions indicate the need for targeted interventions to enhance the quality and competitiveness of the destination. Therefore, this program aims to provide solutions through several initiatives: (1) socialization to increase community awareness of the benefits of tourism, (2) development of water-based attractions such as lake tours using traditional boats, canoes, and paddle boats, as well as traditional rinuak fishing and recreational fishing, and (3) training for water tourism guides and first aid (PPGD) for tourists. This program is expected to strengthen community capacity and improve the sustainability and attractiveness of the destination